2019
DOI: 10.1016/j.yjmcc.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming orchestrates CD4+ T-cell immunological status and restores cardiac dysfunction in autoimmune induced-dilated cardiomyopathy mice

Abstract: Cellular autoimmune responses, especially those mediated by T-cells, play vital roles in the immunopathogenesis of dilated cardiomyopathy (DCM). Metabolic reprogramming directly controls T-cell function, imprinting distinct functional fates. However, its contribution to T-cell dysfunction and the immunopathogenesis of DCM is unknown. Here, we found that in DCM patients, CD4 + T-cells exhibited immune dysfunction and glycolytic metabolic reprogramming based on extracellular acidification and oxygen consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine directly controls the immune status of CD4+ T cells. e adoptive transfer of CD4+ T cells from DCM mice to normal receptors causes cardiac remodeling and cardiac T cell dysfunction [62]. Inflammation is crucial in the early development and progression of many cardiovascular diseases involving congenital and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-Based Complementary and Alternative Medicine directly controls the immune status of CD4+ T cells. e adoptive transfer of CD4+ T cells from DCM mice to normal receptors causes cardiac remodeling and cardiac T cell dysfunction [62]. Inflammation is crucial in the early development and progression of many cardiovascular diseases involving congenital and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The TREG cells play an essential role in inducing and maintaining immune homeostasis and tolerance. The generation or dysfunction of Treg cells can trigger abnormal immune responses and lead to pathology [ 62 ]. Myocardial diseases, such as DCM, are characterized by chronic inflammation, mainly mediated by T lymphocytes, and associated enhanced reactive fibrosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Previous studies have demonstrated that glycolytic metabolic reprogramming is essential for EAM-induced cardiac remodeling. 11 Furthermore, the T cell immunological and metabolic status is associated with the course of EAM progression. [11][12][13][14] Recently, the critical involvement of cell-cell communication has been suggested in a variety of pathophysiological processes, resulting in novel interventional targets.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, the T cell immunological and metabolic status is associated with the course of EAM progression. [11][12][13][14] Recently, the critical involvement of cell-cell communication has been suggested in a variety of pathophysiological processes, resulting in novel interventional targets. 15 Exosomes are one example of this.…”
Section: Introductionmentioning
confidence: 99%
“…The status of cancer cells can be reprogrammed through metabolic remodeling while their dedifferentiation ability for the induced stem-like phenotype is maintained [2022]. This capability of switching between differentiated somatic and stem cell states is called cell plasticity [23].…”
Section: Introductionmentioning
confidence: 99%